Pelatihan Manajemen Pemeliharaan Ayam Jantan Petelur pada Kelompok Ternak Nawawi Farm Jember - M. Adhyatma; Gayuh Syaikhullah; Rizki Amalia Nurfitriani; Nur Muhamad; Satria Budi Kusuma (Journal of Community Development, 2020)
"Nawawi Farm" Breeder Group of Nogosari Village is one of the breeder's groups community in Jember Regency which has a focus on layer rooster’s commodity business. Members of this group are approximately 100 breeders. Production of laying hens has a final weight of around 800 g. Meanwhile, feeding during maintenance requires quite a lot of cost. The existence of expenditures made and income generated is unbalanced, of course, become quite serious problems in the world of the livestock business. This is due to the lack of understanding of the Nawawi Farm livestock group regarding the maintenance management of Laying Roosters. Therefore, training and educations are needed regarding the maintenance management of laying hens. The service of the community dedication stage begins with analyzing community needs, training in the management of laying hens, to guiding the maintenance of laying hens in the Nawawi Farm Livestock Group. The main results of the implementation of this service carried out is that all Nawawi Farm breeders can understand the maintenance management of Laying Hens properly and correctly. The service activities that have been carried out can be carried out properly and run smoothly in accordance with the planned activities that have been prepared. This community service activity was well-received by all apparatus of the Nawawi Farm breeder group. The suggestion of this activity is a follow-up activity in the form of training on making rations with the use of local feed ingredients, especially in the face of the new normal era now to maintain the economic stability of the Nawawi Farm livestock group.